POTENSI BERKEMBANGNYA INOVASI PEMBANGUNAN DAERAH BERDASARKAN AKTIVITAS PENELITIAN PERGURUAN TINGGI DI KABUPATEN PRINGSEWU - Surya Tri Esthi Wira Hutama (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
Decentralization policies provide regional authorities the ability to manage their potentials and problems independently. The unequal geographical, social and economic conditions are challenges for every local government in solving problems and developing their own potential. In responding to these challenges, innovations that are practical and appropriately relevant to directly solve the problems in the region are needed. Innovations are generated through a series of scientific studies or research. In its implementation, the process of generating innovation can be designed systematically, known as RIS (Regional Innovation System). Research activity is one of the components carried out by academics in providing input for practitioners and the government in producing innovations. This research discusses how research activities were carried out in Pringsewu Regency to giude local stakeholders to promote innovations in their development and managerial approaches. The identification process is carried out by mapping various research that have been published in the last 5 years, to understand the direction of regional development through research activities. The linkage can be justified as a potential framework of innovation in Pringsewu Regency. Research activities in Pringsewu Regency, according to the identification process, are dominantly carried out in the health, education and agriculture sectors. This focus is in line with the development direction of Pringsewu Regency which is oriented towards the local economy and the quality of human resources. The overall findings suggest that the research focus in health, education and agriculture emerged as the fundamental elements of local innovations in Pringsewu’s development